The Claims of Labour: An essay on the duties of the employers to the employed - Helps, Arthur, Sir, 1813-1875 (Salt Lake City, UT : Project Gutenberg, 2009)
"The Claims of Labour: An Essay on the Duties of the Employers to the Employed" is an essay written in the mid-19th century that discusses the responsibilities of employers toward their employees. The text delves into the evolving relationship between workers and their employers, emphasizing the duty of the latter to safeguard the welfare and dignity of the labouring classes. It addresses the pressing social issues of its time, particularly concerning the living and working conditions of the working people. The opening of the essay establishes its foundational ideas by framing the employer-employee relationship as a vital yet often misunderstood dynamic in society. The author reflects on the social changes occurring at the time, pointing out the declining closeness between employers and employees and the increased need for benevolence and moral responsibility in such interactions. Through various examples and philosophical reflections, the author argues that understanding these duties is essential in creating a harmonious society, calling for employers to recognize their roles in improving the conditions for the labourers they depend upon. (This is an automatically generated summary.)
Release date is 2009-10-12
Transcribed from the 1845 William Pickering edition by David Price
Keywords: Industrial relations; Working class